Cultivating value from waste: creating novel food, feed, and industrial applications from bambara groundnut by-products - Lungaho, M.; Ojuederie, O.B.; Kareem, K.T.; Odesola, K.A.; Popoola, J.O.; Onawo, L.O.; Igiebor, F.A.; Uselu, A.; Adegboyega, T.T.; Ikhajiagbe, B. (2025)
Bambara groundnut (Vigna subterranea), a vital yet underutilized African legume, significantly boosts food security due to its nutritional value and adaptability to harsh climates and soils. However, its processing yields substantial waste like husks, shells, and haulms, which are often carelessly discarded, causing environmental damage. This paper highlights the urgent need to valorize these waste streams to unlock sustainable growth and economic development. Given their lignocellulosic composition, Bambara groundnut residues are ideal for generating biogas and bioethanol. Beyond energy, these wastes can be transformed into various bio-based products, including adsorbents for heavy metal removal, activated carbon for water purification, and bioplastics. Their inherent nutritional content also allows for the extraction of valuable components like dietary fiber, protein concentrates, and phenolic compounds for food products or animal feed. The nutrient-rich organic matter can also be composted into fertilizer, improving soil fertility. These valorization strategies offer multiple benefits, such as reduced waste, less environmental contamination, and lower greenhouse gas emissions, alongside new revenue streams for agricultural producers. This integrated approach aligns perfectly with circular economy principles, promoting resource efficiency and maximizing agricultural utility. Despite challenges like anti-nutritional factors and processing costs, strategic investments in technology, infrastructure, and supportive policies can unlock Bambara groundnut’s potential for sustainable innovation, job creation, and enhanced food system resilience across Africa and globally. Ultimately, valorizing Bambara groundnut waste presents a transformative opportunity for sustainable growth and improved food systems, particularly within African agriculture.